Cinematic Mythmaking in Andrey Zvyagintsev's The Return and The Banishment - Louis Samuel Mealing (Film-Philosophy)
Since his debut feature The Return (2003), Andrey Zvyagintsev's films have drawn focus from film critics and theorists seeking to investigate a contextual analysis or the director's religious allusions. Hailed as the New Tarkovsky by some, a western-centric perspective has placed Zvyagintsev within the Russian canon from which he originates. However, in doing so, there has been a tendency to overlook a form and aesthetic that seeks to avoid these categorisations. By attempting to engage with his films independently from these frameworks and from a purely humanist perspective of subjectivity, the depth of Zvyagintsev's cinema comes to the surface. We find that the metaphysical reflections of Zvyagintsev's films relate not only to the cinema and its artificial worlds, but also to the position of the human in the real world. Independent of a prior historical or religious perspective, this metaphysical relationship to Zvyagintsev's films focuses on the human and the human consciousness. This article will engage with Zvyagintsev's first two features, The Return (2003) and The Banishment (2007), considering metaphysical aphorisms of one of Zvyagintsev's constant reference points, Georgian philosopher Merab Mamardashvili. This will allow us the opportunity to rethink the relations between cinematic form, the human and the consciousness.